Sleep Is Compromised in −12° Head Down Tilt Position - Boschert, Alessa L.; Elmenhorst, David; Gauger, Peter; Li, Zhili; Garcia-Gutierrez, Maria T.; Gerlach, Darius; Johannes, Bernd; Zange, Jochen; Bauer, Andreas; Rittweger, Jörn (Frontiers in Physiology, 2019)
Recent studies are elucidating the interrelation between sleep, cranial perfusion and cerebrospinal fluid circulation. Head down tilt as a simulation of microgravity reduces cranial perfusion. Therefore, our aim was to assess whether head down tilt is affecting sleep (clinicaltrials.gov; identifier NCT 02976168). 11 male subjects were recruited for a cross-over designed study. Each subject participated in two campaigns each comprising three days and two nights. Intervention started on the second campaign day and consisted of maintenance of horizontal position or -12° HDT for 21 hours. Ultrasound measurements were performed before, at the beginning and the end of intervention. Polysomnographic measurements were assessed in the second night which was either spent in horizontal posture or at -12° head down tilt. Endpoints were sleep efficiency, sleep onset latency, number of sleep state changes and arousals, percentages of N3, REM, light sleep stages and subjective sleep parameters. N3 and REM sleep reduced by 25.6 min and 19.1 min, respectively ((P= 0.002, g= -0.898; P= 0.035, g= -0.634) during -12° head down tilt. Light sleep (N1/2) increased by 33.0 min at -12° head down tilt (P= 0.002, g= 1.078). On a scale from 1 to 9 subjective sleep quality deteriorated by 1.3 points during -12° head down tilt (P= 0.047, g= -0.968). Ultrasonic measurement of the venous system showed a significant increase of the minimum (P= 0.009, P< 0.001) and maximum (P= 0.004, P= 0.002) cross-sectional area of the internal jugular vein at -12° head down tilt. The minimum cross-sectional area of the external jugular vein differed significantly between conditions over time (P= 0.001) whereas frontal skin tissue thickness was not significantly different between conditions (P= 0.077, P= 0.811). Data suggests venous congestion at -12° head down tilt. Since subjects felt comfortable with lying in -12° head down tilt under our experimental conditions, this posture only moderately deteriorates sleep. Obviously, the human body can almost compensate the several fold effects of gravity in head down tilt posture like an affected cerebrospinal fluid circulation, airway obstruction, unusual patterns of propioception and effects on the cardiovascular system.